High Performance Concrete Technology and Applications - Yilmaz, Salih; Baytan Ozmen, Hayri (IntechOpen, 2016)
Concrete is widely used because of its versatility, affordability, and availability of raw materials, strength, and durability. Urban development that took place through the world in the last few decades yielded significant developments for concrete technology. The term high-performance concrete (HPC) is relatively new, and it refers to many properties such as strength, durability, sound and heat insulation, waterproofing, and side advantages such as air purification, self-cleaning, etc. Researchers and engineers are constantly working for improving concrete properties. This book provides the state of the art on recent progress in the high-performance concrete applications written by researchers and experts of the field. The book should be useful to graduate students, researchers, and practicing engineers in related fields.